3D compaction printing of a continuous carbon fiber reinforced thermoplastic. (October 2020) - Ueda, Masahito; Kishimoto, Shun; Yamawaki, Masao; Matsuzaki, Ryosuke; Todoroki, Akira; Hirano, Yoshiyasu; Le Duigou, Antoine
Abstract: This study reports a three-dimensional compaction printing (3DCP) technique for a continuous carbon fiber reinforced thermoplastic (CFRTP). A hot-compaction roller was equipped with a fused filament fabrication (FFF)-based 3D printer to press the filament against the printer bed immediately after the printing to reduce voids and improve adhesion between the filaments. Unidirectional CFRTP coupon specimens were fabricated and the tensile and bending properties of the specimens were investigated. The test results showed that the tensile and bending properties of the printed CFRTP were improved by the hot compaction during 3D printing. Voids in the specimen were visualized using scanning electron microscopy and X-ray computed tomography, and it was confirmed that the hot compaction reduced the void content. The experimental results showed that 3DCP was superior to conventional FFF in the fabrication of CFRTP parts for structural applications.